Placing Elsewhere: Approaches for Physical and Digital Flânerie - Dann, Ying-Lan; Lambrou, Liz (Interiority, 2020)
This paper will discuss approaches and tools for physical and digital flânerie that emerged within an RMIT second- and third-year Interior Design Studio, during the COVID-19 pandemic. In the third week of classes in March 2020, social distancing measures in Australia led us to transpose urban site-based student projects online. Though unforeseen, this was taken as an opportunity for the interior design studio to explicate modes of physical and digital flânerie, via meandering and looking. We discuss teaching and learning experiences within the digital classroom, which we discovered was a dynamic chat-scape of hyperlinks, fragments, displacements and delays. We discuss how we translated aspects of the philosopher Walter Benjamin’s flaneur with reference to The Arcades Project. The paper is structured as a stroll through key discoveries and works and aims to explicate emerging frameworks for digital flânerie within the teaching and learning of interior design.